SERUM OF EXTRACT Onchidium Typhae USES HYDROXYETHYL CELLULOSE AND CARBOXYMETHYL CELLULOSE NATRIUM BASE AS ANTIOXIDANT - Bambang Wijianto; Liza Pratiwi (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Antioxidants can prevent premature aging (anti-aging) and various types of cancer and increase body immunity. Empirically, Onchidiid slugs have been used as natural antioxidants. This study aimed to determine the antioxidant potency of the serum of Onchidiid slug ethanolic extract. The Onchidiid slug extract was obtained by maceration and was prepared to create two effective serum formulations. Formula A involved hydroxyethyl cellulose (HEC), while Formula B employed sodium carboxymethyl cellulose (Na-CMC) as gelling agent. The second serum formula was rigorously evaluated and subjected to antioxidant activity testing by the diphenyl-2-picrylhydrazyl (DPPH) method. The serum preparation with the best physical properties and antioxidant activity was serum A at a concentration of 1%. Physical test results showed that serum A had a yellow color with a distinctive smell and was homogeneous with a soft texture. The test results for the spreadability and stickiness properties of serum A were 6 cm2 and 1'55'' second. The serum A antioxidant activity test results showed moderate free-radical scavenging activity, with an IC50 value of 277 ppm. Keywords: Anti-aging, 2,2-diphenyl-1-pikrilhidrazyl, Onchidium typhae, Antioxidant